Doctor! Did you Google my symptoms? A qualitative study of patient perceptions of doctors’ point-of-care information seeking - Mieke L van Driel; Isaac Tranter; Ben Mitchell (BMJ Open)
Objective To explore patient perceptions regarding doctors’ information seeking during consultations.Design and setting Qualitative interviews with participants from six general practice waiting rooms in South East Queensland, Australia. Participants were asked about their experiences and opinions, and to comment on short videos of simulated consultations in which a doctor sought information. The interviews were analysed through a process of iterative thematic analysis using the framework of Braun and Clarke.Participants The 16 participants were purposively sampled including 5 men and 11 women from a diverse range of educational and age groups.Results How a doctor’s need to look up information impacted patient impressions of competence and trust was an overarching theme. The four dominant themes include: the trust a patient has in the doctor before the consultation, whether the doctor is expected to know the answer to a question without searching, has the doctor added value to the consultation by searching and the consultation skills used in the process.Conclusions Patient trust is fundamental to positive perceptions of general practitioners’ information seeking at the point-of-care. Communication is key to building this trust. Understanding the patient’s agenda, listening, assessing thoroughly and being honest and transparent about the need to seek information all contribute to a positive experience.